THE EFFECT OF MONOPOLY GAME SIMULATION IN THE STAD TYPE COOPERATIVE LEARNING MODEL ON THE LEARNING OUTCOMES OF MIDDLE SCHOOL STUDENTS - Diana Ayu Lestari; Zetriuslita (UIR PRESS, 2021)
This study aims to determine the effect of the simulation game monopoly in the STAD type cooperative learning model on the learning outcomes of junior high school students. The population in this study were all class VIII SMPN 4 Bathin Solapan for the 2018/2019 academic year. The samples in this study were students of class VIII-4 as the experimental class and VIII-5 as the control class. This type of research is a quasi-experimental study with a Noneequivalent control group design. The sampling technique used was a random sample technique. The data collection instruments used in this study were pretest and posttest sheets. The data analysis technique used is inferential statistical analysis. From the N-gain data for both classes, it is obtained t-count>t-table. This means rejected means that there is a significant difference between the learning outcomes of the experimental class and the control class. This shows that there is an effect of the monopoly game simulation in the STAD type cooperative learning model in this study on the learning outcomes of junior high school students